First steps towards assessing the radiation budget in the shelf areas of the Laptev Sea by remote sensing and radiative transfer modelling - Pefanis, Vasileios; Altenburg Soppa, Mariana; Hellmann, Sebastian; Hoelemann, Jens; Janout, Markus; Martynov, Fedor; Heim, Birgit; Rozanov, Vladimir; Loza, Svetlana; Dinter, Tilman; Bracher, Astrid (2018)
The Arctic Ocean receives considerable input of terrigenous carbon supplied by the Arctic rivers. In the context of climate change and thawing permafrost in Eastern Siberia, freshwater discharge and subsequently the riverine input may increase in the future, affecting the radiation budget in the region. Here, we examine the effect of the water optically active constituents on the radiation budget of the Laptev Sea surface waters. We use a coupled atmosphere-ocean radiative transfer model (RTM), MERIS data and in situ measurements of CDOM absorption (aCDOM), total suspended matter (TSM) and chlorophyll concentration (Chla) to simulate the radiative heating. As a first step, we evaluate RTM simulation capabilities by implementing MERIS imaging geometry and collocating every in-situ station to MERIS data to simulate the top of the atmosphere radiance. Additionally, we demonstrate the significant influence of CDOM and TSM on the energy budget of the Laptev Sea surface waters. Results show that high CDOM absorption may lead to 11.4% more absorbed energy in the surface layer (upper 2m) compared to low CDOM waters, which corresponds to an increased heating rate of about 1.3°C/day. Regarding TSM, high concentration leads to an increase of 10.6% in the absorbed energy and 1.2°C/day in the heating rate compared to low concentrations, while the impact of phytoplankton is almost negligible. As more energy is trapped in the surface, cooling occurs in the sub-surface layer (>2m). We further examine the influence of the absorbed solar energy on the melting of sea ice and the induced surface fluxes to the atmosphere. In addition, using satellite remote sensing retrievals of aCDOM, TSM, Chla and sea surface temperature data as input to the RTM simulations, we present the spatial distribution of potential radiative heating of Laptev Sea surface waters.